Uji Kualitatif dan Organoleptik Kandungan Formalin pada Hasil Laut yang Dikeringkan Berupa Ikan Teri, Cumi, dan Rebon dari Pasar Pagesangan - Ratulangi, Wulan Ratia; Widyan, Rosnalia (Puslitbang Sekawan Institute Nusa Tenggara, 2024)
Food additives are often found in every processed food product. However, it is not uncommon for business actors to use prohibited food additives in the form of formaldehyde which is used as a preservative in plywood, foam and so on, but is used to preserve food in the form of dried seafood. Dried sea products in the form of anchovies, squid and rebon itself are one of the foodstuffs that are popular with the public and processed into delicious local food. This research aims to carry out qualitative and organoleptic tests for the formaldehyde content of dried marine products in the form of anchovies, squid and rebon obtained from several traders at Pagesangan Market, Mataram City, West Nusa Tenggara. Sampling was carried out using random sampling technique. The formalin qualitative test on salted fish samples was carried out by adding 1 ml of Fehling A and Fehling B. A positive test was indicated by the color of the blue solution changing to green and the presence of a brick red precipitate. Apart from that, it is also supported by the results of organoleptic tests which include color, aroma, shape or texture. The total number of samples tested was 15 samples obtained from several different traders, where 7 samples were positive for formalin. This can be seen from the physical characteristics of anchovies, squid and rebon with a bright white and fresh color, the odorless aroma of marine products preserved in salt, and the shape or texture is smoother, more intact and does not break easily compared to the sample. negative for formalin.